Cross-reactivity between the immunodominant determinant of the antigen I component of Streptococcus sobrinus SpaA protein and surface antigens from other members of the Streptococcus mutans group. - Goldschmidt, R M (1990)
Most members of the Streptococcus mutans group of microorganisms specify a major cell surface-associated protein, SpaA, that is defined by its antigenic properties. The region of the spaA gene from Streptococcus sobrinus 6715 encoding the immunodominant determinant of the major antigenic component (antigen I) of the SpaA protein has recently been characterized. This study examined whether recognition of the immunodominant determinant is independent of the immunized animal host and whether antibodies elicited by the immunodominant determinant cross-react with cell surface proteins from S. mutans of various serotypes. Mouse and rabbit antisera to the undenatured SpaA protein reacted similarly both with the immunodominant determinant and with other antigenic structures of the protein in Western immunoblots with SpaA polypeptides that were specified by spaA gene fragments expressed in recombinant Escherichia coli. This suggests that the antibody responses of inbred and outbred animals were similar. Furthermore, antibodies raised against both the S. sobrinus SpaA immunodominant determinant expressed by recombinant E. coli and the purified protein from S. sobrinus displayed similar strain specificities and protein band profiles towards cells surface proteins from S. mutans of various serotypes in immunodot and Western blot analyses, respectively. This suggests that for S. sobrinus serotype g, the immune response against the SpaA protein is governed by the immunodominant determinant of antigen I. In addition, it indicates that the SpaA protein domain containing the immunodominant determinant overlaps the domain conferring cross-reactivity to cell surface proteins of S. mutans of various serotypes.